The Impact of Social Security on Return Migration among Latin American Elderly in the U.S. - Vega, Alma (Popul Res Policy Rev, 2014)
International migration has long been considered the preserve of working-age adults. However, the rapid diversification of the elderly population calls for increased attention to the migration patterns of this group and its possible motivations. This study examines whether Latin American immigrants who are primary Social Security beneficiaries are more likely to return to their home countries during later life if they receive lower Social Security benefits. Using a regression discontinuity approach on restricted data from the U.S. Social Security Administration (N=1,515), this study presents the results of a natural experiment whereby the Social Security Administration unexpectedly lowered the Social Security benefits of the 1917-1921 birth cohorts due to a miscalculation in the benefit-calculation formula. Results suggest that approximately 10% of primary Social Security beneficiaries from Latin America born close to these dates return migrated, the probability of which was not affected by Social Security benefit levels.